Child Poverty : Aspiring to Survive - Treanor, Morag (Book collections on Project MUSE., 2020)
"Child poverty is rising across affluent western societies and how it is measured is vital to how governments act to prevent, alleviate or eliminate it. While the roots of childhood poverty are fiercely debated and contested, they are all too often misrepresented in policy and media discourses. Seeking to redress this, Treanor places children's experiences, needs and concerns at the center of this critical examination of the contemporary policies and political discourses surrounding poverty in childhood. She examines a broad range of structural, institutional and ideological factors common across developed nations, and their impacts, to interrogate how poverty in childhood is conceptualized and operationalized in policy and forge a radical pathway for an alternative future." --